Relevance and prospect of development of imitating modelling at research of working process of the excavator - B. H. Kuznetsova; V. V. Savinkin; A. R. Ilyasova (Вестник СибАДИ)
In carrying out the most energy-intensive operations (introduction of the bucket into the ground and peel shavings) on the working of the excavator body are alternating loads, causing the tension elements of the bucket and the working equipment. Reliability and availability of the excavator and the energy intensity of the workflow depends on the validity of the acceptable values of loads and redistribution of the elements of the work equipment taking into account the safety factor. The article substantiates the relevance and perspective shovel energy research. According to the research the technique of experimental studies, combined with simulation modeling shovel loading conditions.